QUALITATIVE CHARACTERISTIC OF DEWLAP, HORNS, AND DOUBLE MUSCLE OF PERANAKAN ONGOLE AND BELGIAN BLUE CROSSBRED IN WEST JAVA - Bestyan, Adam; Arifin, Johar; Edianingsih, Primiani (Jurnal Produksi Ternak Terapan, 2024)
ABSTRACTThe Purpose of this study was to determine qualitative characteristic of dewlap, horns, and double muscle point of Peranakan Ongole and Belgian Blue crossbred in west java. This study was carried out in April – May 2022. This crossbred is spread across all four boroughs in West Java, other things: Ciamis Regency, Tasikmalaya Regency, Garut Regency and Purwakarta Regency. The method used is descriptive exploratory. The number of samples was 18 aged 1-9 months. Data collected: exist or doesn’t exist of dewlap, exist or doesn’t exist of horn’s, and exist or doesn’t exist of double muscle. The data obtained were analyzed using relative frequency. Relative frequency table shows that Belgian Blue Cattle and their crosses with Peranakan Ongole have 100 % dewlap are exist, 77,7 % horn are exist and 16,67 % double muscle are exist.